Implementation of Human Resource Management in the Growth of Digital Personal Shopper - Artana Diva Syabilla; Rhian Indradewa; Ferryal Abadi; Unggul Kustiawan (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Human Resource Management (HRM) plays a crucial role in the success of organizations, especially in the era of globalization. This article discusses the initial 5 years HRM strategies implemented by TITIP application, a technology-based digital personal shopper service company. TITIP aligns its vision, mission, and company objectives with human resource management, including recruitment, training, and the development of an innovative work culture through systematic planning. This research demonstrates that HRM strategies create an inclusive work environment and encourage employee participation. By emphasizing the company's values of being ‘quick, innovative, and easily accessible’, TITIP is able to enhance productivity and create a competitive advantage. These findings highlight the importance of integrating HRM practices within business strategies to achieve growth and sustainability amidst global challenges.